Towards a Review of Key Success Factors in Technology Entrepreneurship - Nina Mihajlović; Sanja Marinković; Jovana Rakićević (Management, 2023)
Research Question: Through a systematic review of the relevant literature, this paper identifies and analyses key success factors in technology entrepreneurship and provides a novel classification and systematization of the factors. Also, it provides a prioritization of the selected factors by tech entrepreneurs. Motivation: The conditions of uncertainty and the dynamic environment in which one technological venture operates cause that only a small number of them succeed (Baron, 2000; Changsok et al., 2012; Tomy & Pardede, 2018; Chen et al., 2019). Comprehensive systematization of success factors is lacking in the professional literature. This paper contributes to the literature in this field by systematizing and prioritizing the key success factors in technological entrepreneurship, as a usable basis for further research and decision making. Idea: The core idea of this paper was to provide an overview of existing knowledge and a systematized basis for further research, but also for work in the practice of technological entrepreneurship, giving guidance to all stakeholders and decision makers, entrepreneurs, investors and policymakers. Data: The review was conducted using online repositories of scientific publications on technology entrepreneurship success factors published in the period from 1980 to 2021. In total, 661 articles were identified, while 45 articles met the selection criteria and represent the basis for further research of this paper. In order to determine the prioritization of the identified factors, empirical research was conducted among decision makers of technological entrepreneurial ventures. Tools: The research and review of the literature were conducted by structured keyword search of the Web of Science database, while the process of article selection was performed using the identified selection algorithm, based on two phases, which both included the selection criteria. For the purposes of empirical research, the Google form questionnaire was used for collecting the data on the prioritization of the factors by technology entrepreneurs. Findings: The factors that are key to the success of technology ventures are often complex in nature. 151 originally identified success factors from different authors were classed into 31 groups. Based on the identified groups, five large groups of factors were used for classification: "characteristics of the founder/founding team", "environment", "technology and innovation", "organization" and "strategy". As a result of empirical research, the factor “motivation” emerges as the most influential factor on a venture’s success, while the “size of the founding team” is identified as the least influential. Contribution: This paper extends the existing literature providing the systematization of key technology entrepreneurship success factors with the systematization of scientific publications as a basis for further research.